2006
DOI: 10.1007/s11010-006-9226-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin C on muscle glycogen and oxidative events in experimental diabetes

Abstract: In the study, 38 male adult Wistar Albino rats with weights 200 +/- 20 g were used by separating them into four groups: Control, Vitamin C, Diabetes, Diabetes + Vitamin C. Body weights and fasting blood glucose were measured at the beginning and end of the experiment. AA, TBARS, GSH, NOx and glycogen levels of soleus muscles, and AA level of blood were measured. The results were compared using Anova variance and Mann-Whitney U tests. Results showed that AA levels in blood increased with vitamin C administratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
2
0
5
Order By: Relevance
“…Significantly lowered levels of hepatic ascorbic acid in diabetic animals and humans have been reported to contribute to the complications arising at later stages in the progression of diabetes (Bulduk et al, 2006;Will and Byers, 1996;Kashiba et al, 2000). Presently, the significant improvement in ascorbic acid levels in liver of diabetic rats administered with LCLEt (300 and 450 mg kg −1 bw in IDDM; 450 mg kg −1 bw in NIDDM) compared to that in controls, could be due to reduced oxidative stress and restoration of hepatic functions.…”
Section: Discussionmentioning
confidence: 85%
“…Significantly lowered levels of hepatic ascorbic acid in diabetic animals and humans have been reported to contribute to the complications arising at later stages in the progression of diabetes (Bulduk et al, 2006;Will and Byers, 1996;Kashiba et al, 2000). Presently, the significant improvement in ascorbic acid levels in liver of diabetic rats administered with LCLEt (300 and 450 mg kg −1 bw in IDDM; 450 mg kg −1 bw in NIDDM) compared to that in controls, could be due to reduced oxidative stress and restoration of hepatic functions.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, vitamin C, applied at 100-200 mg/kg, prevented the increase of the serum creatinine and decrease of creatinine clearance better than the vitamin C applied at 50 mg/kg doses. Recently, Bulduk et al [45] reported that vitamin C, with 20 mg/kg dosages, partially corrected the plasma vitamin C levels and oxidative events in streptozotocininduced diabetic rats. In the present study, vitamin C, in 20 mg/kg dosages, significantly reduced MDA levels when compared with saline-treated rats, whereas MDA levels in the vitamin C group were found to be significantly higher than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle kas kaybı, kas güçsüzlüğü ve atrofisi diyabet ile karakterize önemli belirtilerdir. Deneysel ve doğal diyabette, iskelet kasında ortaya çıkan kayıplar protein katabolizmasındaki artış ile birlikte görülmektedir [3].…”
Section: Diyabetin Doku Ve Organ Metabolizması üZerindeki Zararlıunclassified
“…Diyabet ile ilişkili komplikasyonların patolojisinde artmış ya da kontrolsüz oksidatif stres merkezi role sahiptir. Hiperglisemi, vücutta serbest radikaller ile antioksidanlar arasında bulunan dengeyi bozarak reaktif oksijen türlerinin artmasına, antioksidan savunma sisteminin aktivitesinin azalmasına sebep olmaktadır [3]. Streptozotosin (STZ), deney hayvanlarında deneysel diyabet oluşturmada yaygın olarak kullanılan diyabetojenik bir bileşiktir.…”
Section: Diyabetin Doku Ve Organ Metabolizması üZerindeki Zararlıunclassified
See 1 more Smart Citation